LEADERSHIP MUHAMMAD AL-FATIH PENAKLUK KONSTATINOPEL SEBAGAI INSPIRASI PEMIMPIN MUDA ISLAM MODERN - Ahmad Musthofa (STIT Darul Hijrah Martapura, 2021)
The definition of leadership reflects the assumption that leadership involves a deliberate process of someone emphasizing their strong influence over others to guide, organize, and facilitate activities, group dynamics, and relationships or demonstrate similarities. With this in mind, this article describes the leadership of Muhammad al-Fatih, the conqueror of Constantinople, as an inspiration for modern young Islamic leaders. This study uses a qualitative approach and a literature review process. The researchers searched for information from various reference sources in the form of documents and then analyzed and described the information. Based on the results of the discussion, Muhammad Al-Fatih is an inspiration for a perfect leader, as a leader who has a spirit of perseverance and discipline in conquering the fortress of Constantinople, and has a very high level of fortitude and belief. In addition, Muhammad Al-Fatih is an intelligent leader in all fields, always seeking knowledge and having a spirit of perseverance, and a leader with strong faith that nothing can be achieved without the help of Allah SWT.